2021
DOI: 10.1002/dta.3183
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the detection of growth hormone releasing hormone synthetic analogs

Abstract: The administration of growth hormone releasing hormone (GHRH) and its synthetic analogs is prohibited by the World Anti-Doping Agency (WADA). Although there is evidence of their use, based on admissions and intelligence, they do not appear to have been found in anti-doping samples by WADA accredited laboratories. This might be due to their small concentration in urine and limited knowledge about their metabolism, especially for unapproved synthetic analogs. This study investigates the in vitro metabolism and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…15,16,19 Recent in vitro studies have identified metabolites for sermorelin, CJC-1295, CJC-1295-DAC, and tesamorelin. 13 However, in vivo studies were able to detect the parent compounds for CJC-1293, CJC-1295, and tesamorelin in rats for at least 8 h in blood. 20 Previous in vitro studies of MGF R23H suggest that it is stable in plasma and may be detected as the parent compound.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…15,16,19 Recent in vitro studies have identified metabolites for sermorelin, CJC-1295, CJC-1295-DAC, and tesamorelin. 13 However, in vivo studies were able to detect the parent compounds for CJC-1293, CJC-1295, and tesamorelin in rats for at least 8 h in blood. 20 Previous in vitro studies of MGF R23H suggest that it is stable in plasma and may be detected as the parent compound.…”
Section: Introductionmentioning
confidence: 98%
“…A more recent method has described detection of insulin analogues using a solid phase extraction (SPE) method in urine 12 . Additionally, an SPE method for detection of GHRH analogues was recently reported 13 . However, a more comprehensive method that is able to detect several classes of large peptides in urine is needed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Further, the biotransformations of the GHRHs sermorelin, tesamorelin, CJC-1295, and its drug affinity complex product were studied in vitro, followed by synthesis of 19 metabolite candidates and subsequent development of a comprehensive LC-MS/MS-based analytical approach for doping control urine samples. 7 Analytical options for uncovering gene doping practices were shown to be applicable also to dried blood spots (DBS), and a threestep protocol for initial testing and confirmation was presented, facilitating the detection of the erythropoietin transgene using real-time polymerase chain reaction (rt-PCR). 8 Addressing the question whether or not drug residues found in athletes' doping control urine samples are the result of an intentional antidoping rule violation, the unknowing intake of prohibited substances, or the use of a prohibited drug via permissive routes has become a complex task and is difficult to accommodate on the basis of a single analytical test result.…”
mentioning
confidence: 99%